USP26 suppresses type I interferon signaling by targeting TRAF3 for deubiquitination. - Cheng-Lan Sheng; Bang-Dong Jiang; Chun-Qiu Zhang; Jin-Hua Huang; Zi Wang; Chao Xu (PLoS ONE, 2024)
Deubiquitinating enzymes (DUBs) play a pivotal role in regulating the antiviral immune response by targeting members of the RLR signaling pathway. As a pivotal member of the RLR pathway, TRAF3 is essential for activating the MAVS/TBK-1/IRF3 signaling pathway in response to viral infection. Despite its importance, the function of DUBs in the TRAF3-mediated antiviral response is poorly understood. Ubiquitin-specific protease 26 (USP26) regulates the RLR signaling pathway to modulate the antiviral immune response. The results demonstrate that EV71 infection upregulates the expression of USP26. Knockdown of USP26 significantly enhances EV71-induced expression of IFN-β and downstream interferon-stimulated genes (ISGs). Deficiency of USP26 not only inhibits EV71 replication but also weakens the host's resistance to EV71 infection. USP26 physically interacts with TRAF3 and reduces the K63-linked polyubiquitination of TRAF3, thereby promoting pIRF3-mediated antiviral signaling. USP26 physically interacts with TRAF3 and reduces the K63-linked polyubiquitination of TRAF3, thereby promoting pIRF3-mediated antiviral signaling. Conversely, knockdown of USP26 leads to an increase in the K63-linked polyubiquitination of TRAF3. These findings unequivocally establish the essential role of USP26 in RLR signaling and significantly contribute to the understanding of deubiquitination-mediated regulation of innate antiviral responses.